Measuring anxiety disorder in bipolar disorder using EVestG: broad impact of medication groups - Lithgow, Brian J.; Moussavi, Zahra (Frontiers in Neurology, 2024)
Objectives Anxiety disorder is present in approximately half of all bipolar disorder (BD) patients. There are neurologic bases for the comorbidity of balance (vestibular) disorders and anxiety. Our objective is to use electrovestibulography (EVestG), which is predominantly a measure of vestibular neural activity to not only quantitatively detect and measure comorbid anxiety disorder but also to quantitatively measure the impacts of anti-depressant, anti-psychotic, and mood stabilizer medication groups on anxiety measures in BD patients. Methods In a population of 50 (24 with anxiety disorder) depressive phase BD patients, EVestG signals were measured. Participants were labeled depression-wise as anxious or non-anxious using standard questionnaires. Analyses were conducted on the whole dataset as well as on matched (age/gender/MADRS) and “modeled medication-free” subsets. Modulations of the low-frequency EVestG firing pattern data were measured. Findings For BD, the main anxious minus non-anxious difference was the presence of an increase in spectral power proximal to 8–9 Hz, which was best attenuated by mood stabilizers. Novelty This is the first study to use an oto-acoustic physiological measure to quantify anxiety disorder in BD wherein it appears to manifest as a peak proximal to 8–9 Hz which we hypothesize as likely linked to hippocampal theta.